2019
DOI: 10.33073/pjm-2019-038
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Listeria monocytogenes Strains Isolated from Milk and Humans and the Possibility of Milk-Borne Strains Transmission

Abstract: Listeria monocytogenes is the etiological factor of listeriosis. The main source of these organisms is food, including dairy products. The aim was to determine the multiple correlations between the drug susceptibility, virulence genes (VGs), and biofilm formation on silicone teat cups of milk-borne and human L. monocytogenes strains. The spread of L. monocytogenes via contaminated teat rubbers was assessed. The L. monocytogenes strains recovered from milk (18), human blood (10), and the reference strain ATCC®1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…Because these biofilms are persistent for several months or even years, food can be contaminated repeatedly (Markkula et al, 2005). Our research confirms the findings of Skowron et al (2019), who showed that L. monocytogenes of milk origin frequently exhibit biofilm activity and possess a number of genes linked with virulence and antibiotic resistance. Additionally, L. monocytogenes only moderately or weakly produced biofilm on different surfaces in earlier investigations by Djordjevic et al (2002) and Harvey et al (2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because these biofilms are persistent for several months or even years, food can be contaminated repeatedly (Markkula et al, 2005). Our research confirms the findings of Skowron et al (2019), who showed that L. monocytogenes of milk origin frequently exhibit biofilm activity and possess a number of genes linked with virulence and antibiotic resistance. Additionally, L. monocytogenes only moderately or weakly produced biofilm on different surfaces in earlier investigations by Djordjevic et al (2002) and Harvey et al (2007).…”
Section: Discussionsupporting
confidence: 89%
“…The presence of the hlyA gene in all strains examined for our study's virulotyping analysis was consistent with research by Osman et al (2016), Şanlıbaba et al (2018), Owusu-Kwarteng et al (2018), El-Demerdash et al (2019 and Skowron et al (2019). Additionally, it was found that L. monocytogenes' ability to form biofilms is impacted by the presence of the hlyA virulence gene (Price et al, 2018), as this organism is better able to withstand ineffective disinfection during cleaning procedures, which results in the continued presence of L. monocytogenes in the final product.…”
Section: Discussionsupporting
confidence: 87%
“…After exposing the silver‐plated SR surface to L. monocytogenes for 12 h, no live bacteria were detected, demonstrating their bactericidal properties (Jiang et al., 2004). L. monocytogenes was found in the silicone teat cup, which may be caused by insufficient pasteurization or cross‐contamination (Skowron et al., 2019). Furthermore, L. monocytogenes contaminate food on a regular basis, pose a significant risk to public health, and their control is a significant barrier in the food production chain (Galié et al., 2018).…”
Section: Bacterial Biofilm On the Surface Of Srmentioning
confidence: 99%
“…The diseases caused by LM are predominantly treated with drugs, such as penicillin, fluoroquinolones, cephalosporins, and vancomycin ( 12 ). LM carried the plcb and iap genes, which make the bacterium highly resistant to drugs, such as penicillin and erythromycin ( 13 ). L. monocytogenes can cross the intestinal barrier by the active invasion of host cells, which is mainly triggered by internalins InlA and InlB.…”
Section: Introductionmentioning
confidence: 99%